PS7:144 Application of the doris algorithm for the definition of disease remission over a 2-year period in a cohort of italian patients with systemic lupus erythematosus. (21st March 2018) - dall'Ara, F; Andreoli, L; Migliorati, F; Armentaro, G; Fredi, M; Frassi, M; Franceschini, F; Calza, S; Tincani, A
Abstract : Objective: Systemic Lupus Erythematosus (SLE) is characterised by a fluctuating course.To achieve sustained remission is the goal of maintenance treatment. In 2014, an international Task Force named DORIS proposed four definitions of remission. Aim of this study was to evaluate the performance of the DORIS algorithm in comparison to the remission status as defined by clinical judgement. Methods: Monocentric retrospective study. Among all SLE patients followed at the Lupus Clinic between 2014 and 2016, we enrolled patients fulfilling the SLICC 2012 criteria who were visited at least once in 2016 and who had at least 5 biannual medical examinations in the previous 2 years.Remission according to DORIS was defined as a clinical-SLEDAI (cSLEDAI) score equal to zero and Physician Global Assessment (PGA)<0.5. Remission Off treatment: corticosteroids and immunosuppressant-free patients with antimalarials allowed; Remission On treatment: antimalarials and/or daily dose of corticosteroids<5 mg and/or immunosuppressants and/or biologics drugs.'Clinical' remission was defined as the absence of any increase in corticosteroids dosage or any change in immunosuppressants. Results: 85SLE patients were enrolled (95% female). 21% of patients were in remission in all the 5 time-points, 23% never got into remission. 55% of patients satisfied DORIS criteria at least in one time-point. Mean duration of DORIS remission was 9 months.In 169 (40%) visits there was a disagreement between DORIS and Clinical definition of Remission: a) in 2% remission according to DORIS but no clinical remission; b) 98% clinical remission but not according to DORIS. The reasons for discordant results were: a) self-management of steroids dosage and precautionary increase of steroids in the suspect of a flare; b) cSLEDAI >0 in 74%, PGA >0.5 in 47%, daily prednisone >5 mg in 18%.The cSLEDAI items that most contributed to the score were urinary and haematological alterations (figure 1).In 30 visits (16 patients) a clinical definition of remission was given despite a daily prednisone dose higher than 5 mg. Conclusion: Nearly 40% of the visits displayed a disagreement between 'clinical' and DORIS remission.This may be attributable mainly to a different approach in evaluating patients: longitudinal in clinical remission and cross-sectional by DORIS. As compared to 'clinical' remission, DORIS definition: may fail to recognise patients with a chronic stable steroid treatment at medium dosage, due to persistent low disease activity; is less sensitive because of PGA being used as a dichotomous variable with a low threshold; is likely to be scored different than zero because of urinary and haematological alterations.